Over-education in multilingual economies: evidence from Catalonia - Maite Blázquez; Sílvio Rendón (Institute for the Study of Labor (IZA), 2007)
Catalonia's economy is characterized by linguistic diversity and provides a unique opportunity to measure the incidence of language proficiency on over-education, particularly, whether individuals with deficient language skills tend to acquire more formal skills or, on the contrary, become discouraged to attend school. Descriptive evidence suggests the latter, that individuals with better language knowledge are more likely to be over-educated. However, estimating a model that controls for individuals' socio-demographic characteristics reveals the opposite: better language knowledge decreases over-education. This effect, although robust to accounting for endogeneity of language knowledge and significant at the individual level, is mostly non-significant on average.
Keywords: 330; Over-education; language; immigration; skill premium; Überqualifikation; Mehrsprachigkeit; Migranten; Katalonien